A comparison of the adhesive strength of zinc phosphate and self-adhesive resin cement as fiber post cementation materials - Setyawan Bonifacius; Deddy Firman; Hasna Djiab (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: The use of fiber post has become commonplace among dental practitioners due to its several advantages. In accordance with the intended use of post which provides retention for coronal restoration, a cement is used that can provide high quality adhesion. Conventional resin cement has long been adopted as a cementation material for consumer fiber post. However, allowing attachment fiber post failure due to errors in the cementing procedure leads to complications. Purpose: This study aimed to compare the adhesion strength of zinc phosphate cement and self-adhesive resin cement as fiber post cementation material. Both consumer cements were easy to use and cheap. Methods: The samples used numbered up to 20 and were divided into two groups. group 1 used zinc phosphate cement, while group 2 used self-adhesive resin cement. Results: The value of the average adhesion strength of group 1 (zinc phosphate) was 82.65 N, whereas that of group 2 (self-adhesive resin) was 402.81 N. Conclusion: This study concluded that the adhesive strength of self-adhesive resin cement as fiber post cementation material was higher than that of zinc phosphate cement.